Analisis Efektivitas Penagihan Piutang Atas Penjualan pada PT XYZ - Susanti, Lintang Ardhiah; Haryati, Tantina (Jurnal Pengabdian Masyarakat, 2025)
Credit sales are a common strategy used by companies to expand market reach, but they carry the risk of generating accounts receivable that may disrupt cash flow. In this context, the effectiveness of receivables collection becomes crucial, especially with the implementation of digital tax systems such as Coretax. This study aims to evaluate the effectiveness of the receivables collection process at PT XYZ and to identify the influencing factors. A descriptive qualitative method was applied through interviews, observations, and document analysis. The findings show that the company’s collection system operates effectively, with a collection success rate averaging 99%. However, some obstacles stem from technical issues with the Coretax system and delays in supporting documents from clients. Internal factors such as the speed of financial accountability processes and the responsiveness of internal teams also play a significant role. This study offers practical insights into the relationship between tax digitalization and the effectiveness of corporate receivables management.